(untitled) (Computer systems and information technologies, 2021)
The quality control system of printing products is the main part of the process, which performs the task of analyzing the measured quality parameters, determining the causes of identified quality defects and choosing how to eliminate them. After determining the causes of quality changes, the method of their elimination depends on the actions of operational personnel who try to eliminate defects, for example by recalibrating the printing machine, changing environmental conditions, the choice of other consumables.